A Case Study on Nestle - Anshuman Singh; Farah Khalifa Alazmi (Journal of International Conference Proceedings (JICP), 2019)
Nestle was founded in 1866 by Henri Nestle. It started off with one man’s initiative to produce infant formula (for infants who are intolerant to their mothers’ milk) and grew into a multinational corporation worldwide. Nestle has more than 250,000 employees worldwide and factories all around globally. The infant product was so successful that it created demand all over Europe. Eventually This success brought in many business joint ventures and the company underwent many name changes along the way. Nestle started to enhance its product varieties and started to introduce baby cereals, breakfast cereals, chocolates, bottled drinks, beverages, icecreams, dairy products, food seasoning, pet food and many more. The product’s growth was encouraged by aggressive R&D (Research & Development). Nestlé is a successful company that has been around for 145 years and still its headquarter in Vevey,Switzerland. The company’s “objectives are to be recognized as the world leader and Nutrition, Health, and Wellness, trusted by all its stakeholders and to be the reference for financial performance in its industry” .Nestlé Environmental Advisory Group meets regularly to review current environmental issues and to anticipate potential concerns.A Review of the three most recent annual reports, which include the company’s balance sheet and income statement, displayed how Nestlé is trying to be the reference of financial performance in its industry. Reviewing the company’s assets, liabilities, andrevenues reiterates Nestlé’s success over the past couple of years. Today Nestlé is seen across grocery stores; however, the general population identifies them based on their brands.Nestlé’s most recent achievement was the purchase of Kraft Frozen pizza business.